Associations between the Big Five personality traits, testosterone, and cortisol in adolescent male athletes - Crewther, Blair T; Obmiński, Zbigniew; Turowski, Dariusz; Szczepańska, Beata; Mroczkowska, Helena (Biology of Sport, 2024)
Testosterone (T) has been conceptualized as a biomarker of individual differences, yet T associations with the Big Five personality traits are inconsistent. Athletes provide a suitable model for evaluation here, as T co-expresses traits related to male-to-male competition and fitness with cortisol (C) playing a moderating role. This study investigated associations between the Big Five traits, T, and C in adolescent male athletes. One hundred and twenty male ice hockey players (aged 14–19 years) were assessed for blood total (T, C) and free (FT, FC) hormones, body-size dimensions (i.e., body mass, height, body mass index [BMI]), the Big Five personality traits (i.e., extraversion, neuroticism, agreeableness, conscientiousness, openness), and trait anxiety. Correlational and regression (with age and BMI as covariates) analyses identified a positive effect of FT on extraversion, but a negative FT effect on neuroticism and anxiety ( p < 0.05). Significant FT × FC interactions emerged for extraversion and agreeableness. Slope testing revealed that FT had a positive effect on extraversion at the FC mean and +1 SD, and a negative effect on agreeableness with FC at +1 SD. In conclusion, adolescent male athletes with a higher serum FT concentration tended to express higher extraversion, but lower neuroticism and anxiety. The FT association with extraversion was moderated by FC concentration, as was agreeableness. Therefore, high-FT athletes presented a behavioural disposition that favours dominance and resiliency, with some dependencies on FC availability. Since all association effect sizes were weak, replicate studies on larger adolescent samples are needed.